Eye pain and dry eye in patients with fibromyalgia - Schuster, Alexander K.; Wettstein, Markus; Gerhardt, Andreas; Eich, Wolfgang; Bieber, Christiane; Tesarz, Jonas (Pain medicine, 2018)
AbstractObjectives. The aim of this study was to examine visual function and eye symptoms in fibromyalgia patients, with a particular focus on dry eye syndrome
Gesehen am 28.08.2019